2012
DOI: 10.1371/journal.pone.0043355
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Instability and Telomere Fusion of Canine Osteosarcoma Cells

Abstract: Canine osteosarcoma (OSA) is known to present with highly variable and chaotic karyotypes, including hypodiploidy, hyperdiploidy, and increased numbers of metacentric chromosomes. The spectrum of genomic instabilities in canine OSA has significantly augmented the difficulty in clearly defining the biological and clinical significance of the observed cytogenetic abnormalities. In this study, eight canine OSA cell lines were used to investigate telomere fusions by fluorescence in situ hybridization (FISH) using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 49 publications
2
25
0
3
Order By: Relevance
“…The present study used canine OSA cell lines with various radiation sensitivities as reported previously (22). Abrams, D17 and Moresco were fairly resistant to gamma-rays (D 10 =7.12-9.33 Gy), while Grey was relatively radiosensitive (D 10 =2.72 Gy).…”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations
“…The present study used canine OSA cell lines with various radiation sensitivities as reported previously (22). Abrams, D17 and Moresco were fairly resistant to gamma-rays (D 10 =7.12-9.33 Gy), while Grey was relatively radiosensitive (D 10 =2.72 Gy).…”
Section: Resultsmentioning
confidence: 89%
“…Cells were grown in minimal essential media (Invitrogen; Thermo Fisher Scientific, Inc., Waltham, MA, USA) supplemented with 10% (v/v) fetal bovine serum (FBS; Sigma-Aldrich, St. Louis, MO, USA) and 1% (v/v) Pen/Strep and fungizone solution (Invitrogen; Thermo Fisher Scientific, Inc.), and they were maintained in a tissue culture incubator at 37˚C in a 100% humidified atmosphere of 5% CO 2 . The cell doubling times of these cells were 19 h for Abrams, 22 h for D17, 18 h for Grey and 22 h for Moresco (22).…”
Section: Methodsmentioning
confidence: 98%
See 2 more Smart Citations
“…copy-number Imbalanzen (CNI), oder Kopienzahl neutraler chromosomaler Umlagerungen (Negrini et al, 2010;Tang et al, 2010;Angstadt et al, 2011;Maeda et al, 2012). Bei humanen Tumoren sind außerdem tumorspezifische chromosomale Veränderungen beschrieben worden (Beroukhim et al, 2010).…”
Section: Introductionunclassified